AN ASSESSMENT OF HOME ACCIDENTS AMONG UNDER FIVE CHILDREN IN MADAGALI LOCAL GOVERNMENT AREA OF ADAMWA STATE - AMODU MO; YAHYA SJ; BOLORI MT; BELLO M (Ntec Specialist, 2012)
Domestic accidents occur at all ages but the very young and very old are especially susceptible, (children being particularly more susceptible). Young children are naturally curious and explore, and this makes them vulnerable to risks and accidents. Objective; To assess the prevalence of domestic accidents among under five (U5) children in Madagali local government area of Adamawa state and to determine treatment options and outcome of such options. Method: A cross sectional descriptive study was conducted from January to February, 2009 using a pre-tested validated questionnaire to collect data. Four hundred questionnaires were administered, the respondents were selected using multistage sampling methods and data was analyzed using Epi InfoTM version 3.3.2 software 2001. Results: One hundred and sixty one of respondents (40.25%) admitted that there were many cases of accidents in their homes and that boys were the most affected. Animal and insect bites were the commonest accidents encountered with 47 cases (29.2%). Out of the total home accidents recorded, 107 (66.5) sought for orthodox treatment accounting for significant number of hospital visits. A few cases of animal bites were treated traditionally. Conclusion: Home accidents among under fives cause significant morbidity and mortality in the communities. Steps such as health education should be carried out within the LGA to prevent such occurrences to promote the health status within the area